Team assisted individualization (TAI): The effect on students' cognitive learning outcomes - Rengiar, Jimmy Alan; Budirianto, Heru Joko; Krey, Keliopas (Univeritas Papua, 2018)
This research aims to see the effect of Team Assisted Individualization (TAI) learning on students' cognitive learning outcomes. Experimental research has been carried out with a pretest-posttest design on 66 high school students. They were divided into two groups (33 students in the TAI class and 33 students in the non-TAI class). Students' cognitive abilities were measured using twenty multiple-choice questions. Data analysis using t-test until free. The findings showed p > 0.05 for pretest data and p < 0.05 for posttest data. This research found that students' initial abilities were the same, but students' final abilities were different. This experimental research concludes that the achievement of cognitive outcomes of students in the TAI class is better than the achievement of cognitive outcomes of students in the non-TAI class. The differences in learning that occurred in the two classes caused the final results to be significantly different.